Patient Preferences for Lung Cancer Treatment: A Qualitative Study Protocol Among Advanced Lung Cancer Patients - Durosini, Ilaria; Janssens, Rosanne; Arnou, Reinhard; Veldwijk, Jorien; Smith, Meredith Y.; Monzani, Dario; Smith, Ian; Galli, Giulia; Garassino, Marina; Katz, Eva G.; Bailo, Luca; Louis, Evelyne; et al. (Frontiers in Public Health, 2021)
Introduction: Lung cancer is the deadliest and most prevalent cancer worldwide. Lung cancer treatments have different characteristics and are associated with a range of benefits and side effects for patients. Such differences may raise uncertainty among drug developers, regulators, payers, and clinicians regarding the value of these treatments to patients. The value of conducting patient preference studies (using qualitative and/or quantitative methods) for benefits and side effects of different treatment options has been recognized by healthcare stakeholders, such as drug developers, regulators, health technology assessment bodies, and clinicians. Using patient preference studies to inform decisions across the drug life cycle has the potential to improve the way treatments are developed, prescribed, authorized, and reimbursed so that they better meet the needs of patients. However, evidence-based guidelines on how and when to conduct and use these studies in drug decision-making are lacking. As part of the Innovative Medicines Initiative PREFER project, we developed a protocol for a qualitative study that aims to understand which treatment characteristics are most important to lung cancer patients and to develop attributes and levels for inclusion in a subsequent quantitative preference survey. Methods: The study protocol specifies a four-phased approach: i) a scoping literature review of published literature, ii) four focus group discussions with lung cancer patients, iii) two nominal group discussions with lung cancer patients, and iv) multi-stakeholder discussions involving clinicians and preference experts. Discussion: This research protocol will be useful to collect qualitative information on patient preferences for lung cancer treatment. The results of this study are intended to inform a subsequent quantitative preference survey that assesses patient trade-offs regarding lung cancer treatment options. This protocol may assist researchers, drug developers and decision-makers in designing qualitative studies to understand what treatment aspects are most valued by patients in drug development, regulation and reimbursement.